Gordonia hydrophobica Nitrile Hydratase for Amide Preparation from Nitriles - Birgit Grill (MDPI AG, 2021)
The active pharmaceutical ingredient levetiracetam has anticonvulsant properties and is used to treat epilepsies. Herein, we describe the enantioselective preparation of the levetiracetam precursor 2-(pyrrolidine-1-yl)butanamide by enzymatic dynamic kinetic resolution with a nitrile hydratase enzyme. A rare representative of the family of iron-dependent nitrile hydratases from Gordonia hydrophobica (GhNHase) was evaluated for its potential to form 2-(pyrrolidine-1-yl)butanamide in enantioenriched form from the three small, simple molecules, namely, propanal, pyrrolidine and cyanide. The yield and the enantiomeric excess (ee) of the product are determined most significantly by the substrate concentrations, the reaction pH and the biocatalyst amount. GhNHase is also active for the hydration of other nitriles, in particular for the formation of N-heterocyclic amides such as nicotinamide, and may therefore be a tool for the preparation of various APIs.